PODEJŚCIA TEORETYCZNE DO BADANIA DEMOKRATYZACJI I AUTOKRATYZACJI NA POZIOMIE LOKALNYM I REGIONALNYM - Szymański, Adam (Polityka i Społeczeństwo, 2021)
In the literature on democratization and autocratization, one of the areas which clearly shows a gap in the theoretical framework is a very important territorial dimension of theseprocesses. This article is aimed at proposing the theoretical approaches based on two main pillars, which can be used in studies on democratization and autocratization at the subnational levels. The first one refers to democracy and changes of political regimes (approaches to democratization / autocratization and more static issues of the quality of democracy and local democracy). The second one refers to the territorial politics, accounting for the multilevel and network governance as well as theories of decentralization. Eventually, the author also presents possible preliminary directions of research, within which the territorial politics can be either an independent, alternatively intervening variable (studies on causes of changes regarding the political regime) or a dependent variable (analysis of effects of these changes).